Stu Davis: Canada’s Cowboy Troubadour - Silversides, Brock (CAML Review / Revue de l’ACBM, 2019)
This essay is a profile of Stu Davis, a Canadian musical composer, performer, and radio/television host between 1939 and 1971. With his many recordings, constant on-air presence, and easy-going personality, he popularized country and western music to mainstream Canadian (as well as American and European) audiences.